(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The issues of eye injury are fairly well covered in the works of clinical ophthalmologists. However, since personal forensic medical aspects of eye injuries as objects of examination remain without due attention, it should be noted that forensic medical examination in cases of eye injury is associated with certain difficulties in choosing a qualification feature for determining the severity of bodily harm. The aim of the study was to analyze the forensic medical features of eye injuries. The research object was clinical observations of cases of eye injury at the Tashkent City Emergency Hospital in 2019 (table 1). When analyzing the medical records of hospitalized patients, attention was paid to the circumstances of the incident, the type, and nature of eye injuries. During the specified period, 124 victims received inpatient treatment. The majority were men (75%). By age groups, more than two-thirds of the victims were aged 18-39. Representatives of older age groups (50 years and older) accounted for 19.3%. In 68.5% of cases, the injury occurred at home, and in 8.1%, it had an occupational nature. In all other cases, injuries were caused on the street and in other places (stadium, cafe, etc.). When analyzing damaging factors, the prevalence of injuries caused by various blunt objects (48.4%) was found. In 35.5% of observations, injuries were caused by sharp objects. In other cases, thermal and chemical injuries occurred (8.1% each).